2005
DOI: 10.1530/eje.1.01978
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of isoforms of human adiponectin: studies in human subjects and in experimental animals

Abstract: Objective: Little is known of the metabolism of different isoforms of adiponectin. We therefore (a) characterised the size distribution of human adiponectin in relation to gender, body composition and following a challenge with a fat meal or oral glucose in humans, and (b) studied the metabolism of isoforms of human adiponectin in rabbits. Method: Electrophoresis, blotting and chromatography were used to characterise human adiponectin in 36 healthy subjects, including 15 with at least two first-degree relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 34 publications
(44 reference statements)
5
94
0
2
Order By: Relevance
“…In the present study, we analysed a large population of middle-aged Finnish men and women to find out how plasma adiponectin levels are associated with MS defined on the basis of the new criteria. The study allowed us to consider sexspecific differences in adiponectin levels and their interaction with MS. As expected, the adiponectin levels were higher in women than in men (20). In both the sexes, we found that adiponectin was correlated negatively with measures of body fat, fasting plasma glucose and triglycerides and hs-CRP.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, we analysed a large population of middle-aged Finnish men and women to find out how plasma adiponectin levels are associated with MS defined on the basis of the new criteria. The study allowed us to consider sexspecific differences in adiponectin levels and their interaction with MS. As expected, the adiponectin levels were higher in women than in men (20). In both the sexes, we found that adiponectin was correlated negatively with measures of body fat, fasting plasma glucose and triglycerides and hs-CRP.…”
Section: Discussionsupporting
confidence: 83%
“…2). Interestingly, it has been found that females have higher proportions of high molecular weight and hexameric forms of adiponectin and lower proportions of trimers, and that the higher molecular form adiponectin serves as a precursor pool for activation by metabolic stimuli, such as an increased insulin level (20). Therefore, adiponectin could partly explain the better insulin sensitivity of females and could also be one reason why lower adiponectin levels have more deleterious effects in women.…”
Section: Discussionmentioning
confidence: 99%
“…Women have more HMW adiponectin than men (23), which may partly explain the differences that we have found between men and women.…”
Section: Results -Baseline Characteristics Are Shown Inmentioning
confidence: 66%
“…Recent work has shown that adiponectin exists in different isoforms, low-molecular weight and highmolecular weight (HMW) complexes (2). Diabetic patients had a significantly decreased HMW-to-total adiponectin ratio (23), and HMW adiponectin correlated better with glucose tolerance than total adiponectin in Indo-Asian males (24). Also, a relatively larger increase in HMW adiponectin after weight reduction has been shown (25).…”
Section: Results -Baseline Characteristics Are Shown Inmentioning
confidence: 98%
“…However, further studies are warranted to explore the direct molecular mechanisms by which these forms of circulating adiponectin sensitise muscle to insulin action. Females have higher circulating levels of total adiponectin, and in particular the proportion of HMW and hexameric adiponectin, than do males [1,40,41]. A selective inhibition of the secretion of HMW adiponectin by testosterone may contribute to these differences [42].…”
Section: Discussionmentioning
confidence: 98%